Development of a Job Sheet for Mechanical Measuring Instruments Using Virtual Learning and Project-Based Learning in the Motorcycle Engineering Department at SMK Negeri 2 Palembang - Adel Lia Mardiana; Arwizet K; Refdinal Refdinal; Jonni Mardizal; Abdul Habib Arrasyidi Desky (Postgraduate, University of Mataram, 2026)
This study aims to develop a mechanical measurement practical worksheet integrated with Project-Based Learning (PjBL) and delivered through a Learning Management System (Google Classroom), as well as to examine its validity, practicality, and effectiveness. The study employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages, with PjBL principles embedded in the product design and learning activities. The participants were 35 tenth-grade vocational students (N=35). The results showed that the developed worksheet achieved a very high level of validity based on expert evaluations of media, content, and language, with an average score of 94.6%. In terms of practicality, teacher and student responses reached 92.72% and 93.18%, respectively, both categorized as “very good,” indicating that the worksheet is easy to use and supports flexible practical learning. Regarding effectiveness, students’ learning outcomes improved significantly, with mean scores increasing from 30.92 (pretest) to 86.00 (posttest) and an N-gain of 0.80 (high category). Hypothesis testing confirmed a significant difference (p < 0.05) before and after implementation. In conclusion, the PjBL-integrated mechanical measurement practical worksheet distributed through Google Classroom as an LMS is valid, practical, and effective in improving students’ learning outcomes.